Identification of hub genes and microRNAs with prognostic values in esophageal cancer by integrated analysis - Amir Mokhlesi; Zahra Sharifi; Ahmad Berimipour; Sara Taleahmad; Mahmood Talkhabi (Non-coding RNA Research, 2023)
Esophageal cancer (EC) is the eighth most common cancer in the world, and the sixth most common cause of cancer-related mortality. The aim of the present study was to identify cell and molecular mechanisms involved in EC, and to provide the potential targets for diagnosis and treatment. Here, a microarray dataset (GSE20347) was screened to find differentially expressed genes (DEGs). Different bioinformatic methods were used to analyze the identified DEGs. The up-regulated DEGs were significantly involved in different biological processes and pathways including extracellular matrix organization and ECM-receptor interaction. FN1, CDK1, AURKA, TOP2A, FOXM1, BIRC5, CDC6, UBE2C, TTK, and TPX2 were identified as the most important genes among the up-regulated DEGs. Our analysis showed that has-miR-29a-3p, has-miR-29b-3p, has-miR-29c-3p, and has-miR-767–5p had the largest number of common targets among the up-regulated DEGs. These findings strengthen the understanding of EC development and progression, as well as representing potential markers for EC diagnosis and treatment.